Power distance orientation as an antecedent of individuals' intentions to engage in radical political action. (December 2020) - Travaglino, Giovanni A.; Moon, Chanki
The cultural dimension of power distance refers to individuals' acceptance of power inequalities in society. Countries characterized by high power distance at the collective level face more domestic extremism. However, research has yet to examine how individual differences in power distance orientation may affect individuals' intentions to engage in radical and violent political action. In this research, we test the hypothesis that stronger endorsement of power distance values makes people more prone to express their intentions to engage in radical and violent political action. To test the hypothesis' generalizability across contexts, we sample from 2 countries characterized by different levels of power distance at the collective level, South Korea (higher power distance) and the United States (lower power distance). Studies 1a and 1b were surveys ( N = 1, 214) demonstrating an association between power distance orientation and radical political action over and beyond other known predictors of political participation, including political efficacy, perceived justice, emotions of anger and contempt, political orientation, and social dominance orientation. In Studies 2a–2c ( N = 430; 2c preregistered), priming a higher (vs. lower) power distance orientation heightened individuals' propensity to express the intentions to engage in radical political action. Theoretical implications of the findings, and future research directions, are discussed.